Challenges and opportunities of organic and regional food supply in community catering - Schwardmann, Annika (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2020)
Comparable collaborations between farmers and institutions with communal catering have been less in research focus so far. Within the region of Lüneburg, an example for such a regional-organic cooperation is not known yet. Thus,this work represents the starting point to fill the research gap within the field of sustainable food systems in urban living labs as part of the research project GLOCULL (Globally and Locally-sustainable food-water-energy innovation in Urban Living Labs). The work aims at building up such a regional-organic food cooperation between a local farmer and a kindergarten community catering servicebased on scientific insights and practical persons’ knowledge.
Insights from a literature review for building cooperation between local producers and community catering in kindergartens in the region of Lüneburg as a contribution to food sovereignty and sustainable development